MAPPING POVERTY CHARACTERISTICS IN LAMPUNG PROVINCE USING BIPLOT ANALYSIS - Baniyah, Baniyah; Ningsi, Besse Arnawisuda; Rahman, Andi Nur (Tesseract: International Journal of Geometry and Applied Mathematics, 2023)
Poverty is a condition of inability to meet minimum basic needs such as food, clothing, health, housing and education. This study aimed to determine the mapping of poverty characteristics in Lampung Province using Biplot Analysis. The research data used in this study is secondary data, namely data on district/city poverty characteristics in Lampung Province in 2021 which are sourced from the published BPS Lampung. From the results of the analysis it was found that districts/cities in Lampung Province have similar characteristics which are divided into four parts, namely Quadrant I North Lampung, Mesuji and West Lampung Regencies have similar characteristics of poverty in illiteracy rate (X2), highest diploma owned (X4) and The population is sick and not receiving treatment (X5),  Quadrant II South Lampung, East Lampung, Pringsewu, West Tulang Bawang and Metro City forms its group which means it has no resemblance to any variable because the object is opposite the direction of the variable vector, Quadrant III District Central Lampung, Pesawaran and Bandar Lampung City have a high correlation for women who do not use family planning devices (X6) and building ownership status (X7). X1), Not attending school anymore (X3), Floor area per capita (X8), and Facilities high defecation capacity (X10). Meanwhile, the characteristics of the sick and unmedicated population (X5) and the type of building materials (X9) had a higher diversity than the other variables. These two characteristics vary relatively in 13 regencies and 2 cities in Lampung Province